2012
DOI: 10.1021/bi201743a
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Membrane-Bound Protein Complexes: Detection and Analysis by Single Molecule Diffusion

Abstract: Protein complexes assembled on membrane surfaces regulate a wide array of signaling pathways and cell processes. Thus a molecular understanding of the membrane surface diffusion and regulatory events leading to the assembly of active membrane complexes is crucial to signaling biology and medicine. Here we present a novel single molecule diffusion analysis designed to detect complex formation on supported lipid bilayers. The usefulness of the method is illustrated by detection of an engineered, heterodimeric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(85 citation statements)
references
References 46 publications
6
78
1
Order By: Relevance
“…As in previous studies, single molecule diffusion tracks were recorded with a 20 msec frame rate, and populations of hundreds of tracks were analyzed (1113). A significant advantage of the single molecule analysis is the ability to resolve diffusional heterogeneity and to filter out minor population components exhibiting anomalous diffusion, thereby more accurately defining the diffusion constant of the major component.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in previous studies, single molecule diffusion tracks were recorded with a 20 msec frame rate, and populations of hundreds of tracks were analyzed (1113). A significant advantage of the single molecule analysis is the ability to resolve diffusional heterogeneity and to filter out minor population components exhibiting anomalous diffusion, thereby more accurately defining the diffusion constant of the major component.…”
Section: Resultsmentioning
confidence: 99%
“…Previous exploratory studies have indicated that 2-dimensional diffusion rates of peripheral membrane proteins on planar supported bilayers provide a new window into (i) protein-lipid, (ii) protein-bilayer, and (iii) protein-protein interactions (1013). Each of these interactions can trigger a significant, detectable change in diffusion speed on the supported bilayer surface that provides key insights into a molecular interaction or event.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubating for 2 h at room temperature, liposomes fused on the substrate, and spontaneously formed a supported lipid bilayer (30,31). The bilayer was rinsed thoroughly with water to remove excess liposomes and protein, and then exchanged into HEPES/CaCl 2 buffer at the desired Ca 2þ concentration (32,33). For control experiments, pure DOPC lipid bilayers and DOPC lipid bilayers containing a low concentration of fluorescent DOPE-LR as probes were prepared using the procedure described above.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The lipid bilayer plays a central role in this network by serving as a shared platform for two-dimensional diffusion, thereby enabling the membrane-bound signaling proteins to encounter and bind their membrane-associated, lipid and/or protein effectors and substrates (Ziemba et al, 2013; Ziemba and Falke, 2013; Ziemba et al, 2012; Knight et al, 2010; Knight and Falke, 2009). The resulting, membrane-localized signaling circuit controls actin polymerization, membrane remodeling, and other dynamic processes essential for growth of the leading edge up attractant gradients.…”
Section: The Assembled Leading Edge Signaling Circuitmentioning
confidence: 99%